Apixaban in Comparison to Warfarin for Stroke Prevention in Nonvalvular Atrial Fibrillation: A Systematic Review and Meta-Analysis of Observational Studies - Muhammad U. Siddiqui; David Scalzitti; Zunaira Naeem (Cardiology Research and Practice)
Introduction. Atrial fibrillation leads to increased risk of systemic embolism and stroke. To decrease these adverse events, anticoagulation is routinely prescribed. Nonvitamin K anticoagulants like apixaban and rivaroxaban are becoming popular and being used more frequently nowadays. We here compare the efficacy and safety of apixaban with those of warfarin. Methods and Analysis. This systematic review aims to assess the efficacy and safety of apixaban compared to those of warfarin. Eligible participants were adults diagnosed with nonvalvular atrial fibrillation. The intervention was apixaban, and the comparator was warfarin. The primary efficacy endpoint is the first admission with systemic embolism or stroke, and the primary safety outcome is the occurrence of major bleeding. Relevant studies were searched in the Cochrane Central Register of Controlled Trials, MEDLINE, PubMed, and clinicaltrials.gov. After being independently reviewed by two authors, five articles were included in the systematic review. The risk of bias of included studies was assessed using the Cochrane risk of bias tool and SIGN methodology. The RevMan software was used to assess the effect size and perform meta-analysis. Results. Apixaban was found to be superior to warfarin in terms of safety (RR 0.58; CI 0.52–0.66) but not superior to warfarin in terms of efficacy (RR 0.93; CI 0.70–1.24). Conclusion. Apixaban is superior to warfarin in terms of safety, but no difference in efficacy is noted. The choice of anticoagulation should be individualized based on the risk factor profile of the patient.